Performance of internet finance companies in China - Tian, Zhongkai; Sheikh Hassan, Ahmad Fahmi (Blue Eyes Intelligence Engineering and Sciences Engineering and Sciences Publication - BEIESP, 2019)
Internet finance experienced fast development in the world including China. With around 2000 internet finance companies currently operating in China there is extensive competitions among internet finance companies offering financial services to investors. The paper empirically investigates the determinants of internet finance companies performance based on 330 randomly selected sample data using a linear regression method based on one-month information collected from an online internet finance database. The findings show that the interest rate level, number of projects, and average loan periods play a significant role in the performance of internet finance companies. This investigation could help internet finance companies to adopt effective competitive strategies in order to enhance market performance and at the same time help individual investors to identify good performed companies from the internet finance market…. The joint efforts from both internet finance companies and individual investors will promote the development of internet finance in China and accelerate the revolution of China traditional financial system.